2004
DOI: 10.1002/gcc.20044
|View full text |Cite
|
Sign up to set email alerts
|

TFG is a novel fusion partner of NOR1 in extraskeletal myxoid chondrosarcoma

Abstract: Extraskeletal myxoid chondrosarcoma (EMC) is characterized by recurrent chromosomal translocations resulting in fusions of the nuclear receptor gene NOR1 (also known as CHN or TEC) to various N-terminal partners, including EWS and TAF2N (or RBP56). Significant structural homology of EWS or TAF2N to TLS (or FUS) prompted us to investigate a potential novel gene fusion of NOR1 to TLS in EMCs without detectable known NOR1 fusions. In one of the EMCs examined, our reverse-transcription polymerase chain reaction us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 20 publications
0
63
1
Order By: Relevance
“…Subsequently, additional TFG fusion proteins were isolated from other malignancies, all of which involved the oligomeric amino terminus of TFG (39,40). We recently demonstrated that native TFG functions at sites of vesicle biogenesis on the ER, forming a matrix between ER exit sites and the ER-Golgi intermediate compartment, a key sorting hub for secretory cargoes in metazoan cells (32).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, additional TFG fusion proteins were isolated from other malignancies, all of which involved the oligomeric amino terminus of TFG (39,40). We recently demonstrated that native TFG functions at sites of vesicle biogenesis on the ER, forming a matrix between ER exit sites and the ER-Golgi intermediate compartment, a key sorting hub for secretory cargoes in metazoan cells (32).…”
Section: Resultsmentioning
confidence: 99%
“…TFG is also the fusion partner of ALK kinase in anaplastic large cell lymphomas (13,14), and of NORI in extraskeletal myxoid chondrosarcoma (15). An attractive hypothesis is the possibility that cellular pathways involving TFG protein might be deregulated in tumors carrying TFG rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…TFG is also involved in the generation of a class of ALK oncogenes in anaplastic large cell lymphoma (13,14). Moreover, TFG has been recently detected as a novel fusion partner for NORI in extraskeletal myxoid chondrosarcoma (15). Studies performed on the normal counterpart have shown that the TFG gene is ubiquitously expressed in human adult tissues and that it is conserved among several species, including C. elegans (16).…”
Section: Shp-1 Is a Cytoplasmic Sh2 Domain Containing Protein-tyrosinmentioning
confidence: 99%
“…t(9;22)(q22;q12) and t(9;17)(q22;q11) have not been found in any other tumors. t(9;15)(q22;q21), which results in the TCF12/NR4A3 fusion gene (16,27), and t(3;9)(q12;q22), which results in the TFG/NR4A3 fusion gene (28), were reported in only one case each. It is unclear whether the fusion genes identified in EMC are associated with particular morphological features and clinical significance.…”
Section: Extraskeletal Myxoid Chondrosarcoma Of the Thigh With A T(9;mentioning
confidence: 99%